2009
DOI: 10.1262/jrd.20205
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F<sub>2</sub><sub>&alpha;</sub> Regulates the Nitric Oxide Generating System in Bovine Luteal Endothelial Cells

Abstract: Abstract. The objective of the present study was to elucidate whether luteolytic prostaglandin F2α (PGF) plays roles in regulating the nitric oxide (NO) generating system in luteal endothelial cells (LECs). Reverse transcriptase PCR, immunoblotting and immunostaining revealed the presence of PGF receptor mRNA (521 bp) and protein (64 kDa) in cultured LECs obtained from the mid-stage corpus luteum. When cultured LECs were exposed to 0.1 μM-10 μM PGF, NO production was significantly stimulated by PGF at 24 h. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 51 publications
4
27
0
Order By: Relevance
“…The cultures and passages were repeated until a homogeneous population of pure LECs was obtained. The LECs isolated in the present study were confirmed by immunocytochemical staining for rabbit anti-human von Willebrand factor (factor-VIII, F3520; Sigma-Aldrich) and CD31 expression as reported previously [7,20,21]. The bovine LECs used in the present study correspond to type 1 according to the previous classification reported by Spanel-Borowski and Bosch [22].…”
Section: Bovine Lec Isolation and Cell Culturesupporting
confidence: 83%
See 4 more Smart Citations
“…The cultures and passages were repeated until a homogeneous population of pure LECs was obtained. The LECs isolated in the present study were confirmed by immunocytochemical staining for rabbit anti-human von Willebrand factor (factor-VIII, F3520; Sigma-Aldrich) and CD31 expression as reported previously [7,20,21]. The bovine LECs used in the present study correspond to type 1 according to the previous classification reported by Spanel-Borowski and Bosch [22].…”
Section: Bovine Lec Isolation and Cell Culturesupporting
confidence: 83%
“…PGF and NO may interact and activate LECs and non-LECs to initiate functional and structural luteolysis, as both are produced by LECs. Interestingly, PGF stimulates NO production in cultured bovine LECs [7]. On the other hand, NO increases PGF production in both LSCs [9] and LECs (the present study).…”
Section: Lee Et Al 458supporting
confidence: 53%
See 3 more Smart Citations